RePhyS: a multidisciplinary experience in remote physiological systems laboratory - Barros, C. (2013)
Remote laboratories have been developed to support the students’ learning and to reduce equipment costs. More and more, laboratories play an important role in engineering teaching, since they allow the connection between theory and practice. Actually, there is the necessity to change strategies and methodologies of education. The remote laboratories enable the access to all students any-time, anywhere because they are available on the Internet. This paper presents the firsts developments of an innovative laboratory in the bioengineering area: RePhyS. RePhyS will be a remote laboratory for use in biomedical and physiological systems studies in graduate and postgraduate levels. The user will be allowed to interact with the system parameters, and to control some system variables. This new lab will enable to produce, visualize and analyze, in real-time, results of practical experiences in order to improve students’ activity of learning, and it will provide with an enriched computing environment for sharing results and collaborations.